2021
DOI: 10.36834/cmej.71333
|View full text |Cite
|
Sign up to set email alerts
|

Impact of accreditation on Caribbean medical schools’ processes

Abstract: Background: Caribbean graduates contribute significantly to the US healthcare workforce. The accreditation requirements of local governments vary from one Caribbean island to another island. The Educational Commission for Foreign Medical Graduates (ECFMG) requirement that all future applicants be graduates from accredited medical schools drove Caribbean medical schools to seek accreditation. Accreditation has been found to significantly impact the educational processes of Canadian medical schools. Our study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
11
0
3
Order By: Relevance
“…Accreditation status, more specifically, has been associated with higher first‐attempt pass rates, and certain standards have been reported as associated with better scores 26–28 . A study based on three Caribbean medical schools found that implementing a self‐study committee with a regular data collection and monitoring processes caused a positive impact 29 …”
Section: Quality Assurance Strategies and Their Tensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accreditation status, more specifically, has been associated with higher first‐attempt pass rates, and certain standards have been reported as associated with better scores 26–28 . A study based on three Caribbean medical schools found that implementing a self‐study committee with a regular data collection and monitoring processes caused a positive impact 29 …”
Section: Quality Assurance Strategies and Their Tensionsmentioning
confidence: 99%
“…[26][27][28] A study based on three Caribbean medical schools found that implementing a self-study committee with a regular data collection and monitoring processes caused a positive impact. 29 Crampton et al 30 concluded that quality assurance efforts depend on contextual factors, which determine positive and negative impact. The organisational resistance to external quality assurance (dissociative features) triggers negative mechanisms leading to poor outcomes (limited compliance, resistance).…”
Section: Research On Accreditationmentioning
confidence: 99%
“…O fato de a maioria dos artigos tratar de componentes curriculares isolados, em especial anatomia e patologia, pode indicar uma maior disponibilidade de recursos pedagógicos virtuais para a sua utilização, como atlas 3D, estruturas de realidade virtual e realidade aumentada 45 . Também é possível destacar que uma parte considerável dos artigos abordou o curso de Medicina como um todo 14,15,24,25,28,30,34,41,[46][47][48][49][50][51][52][53] em sua análise, o que é importante para se ter uma observação geral do quadro, mas isso elimina as especificidades de cada área.…”
Section: Discussionunclassified
“…Akreditasi pendidikan tinggi adalah sarana penjaminan mutu kualitas kepada masyarakat atau komunitas pendidikan tertentu, sehingga ini perlu dipertanggungjawabkan perguruan tinggi dengan relevansinya terhadap praktik pendidikan tinggi (Ahn, 2020;Bandiera et al, 2020). Akreditasi sangatlah penting karena memberikan rasa percaya dan penilaian awal kepada masyarakat baik sebelum melakukan pendaftaran maupun kepercayaan terhadap para lulusan dari tempat terakreditasi baik, sehingga akreditasi perlu dimiliki, diperhatikan, dan diperbarui (Arja et al, 2021;Selesho, 2017). Suatu produk memiliki siklus hidup (life cycle) antara lain pengenalan (Introduction), Pertumbuhan (Growth), Kedewasaan (Maturity), dan Penurunan (Decline), sehingga product yang ditawarkan oleh perguruan tinggi juga perlu diperhatikan jumlah peminatnya, sehingga keberadaan program studi atau product tetap bertahan (Prayitno & Lubis, 2020;Wijanarko & Sulistyawati, 2022).…”
Section: Pembahasanunclassified